Improved diagnostic confidence in evaluating bone non-union using virtual monochromatic dual-energy CT. Issue 132 (November 2020) - Donders, J.C.E.; Wellenberg, R.H.H.; Streekstra, G.J.; Maas, M.; Kloen, P.
Highlights: DECT reduces artifacts and improves image quality in patients with metal hardware. DECT improves diagnostic confidence in evaluating impaired fracture healing. Diagnostic confidence is higher for intramedullary nails compared to plates. Diagnostic confidence was similar in evaluating titanium and stainless steel hardware. DECT may facilitate clinical decision-making whether to revise a fixated fracture. Abstract: Purpose: The aim of this study was to determine whether virtual monochromatic dual-energy CT imaging improves the evaluation of suspected non-union of the appendicular skeleton treated with titanium or stainless steel intramedullary nails and plates. Method: Forty-one patients with a clinical suspected non-union with hardware in place were included and scanned on a dual-source CT-scanner using 100/Sn150kVp. Images including titanium hardware were extracted at 130 keV. Images including stainless steel hardware were extracted at 150 keV. Monochromatic 70 keV images served as reference. Non-union confirmed during revision surgery was used as gold standard. A musculoskeletal radiologist and orthopedic trauma surgeon evaluated images on image quality, degree and location of consolidation, non-union type and diagnostic confidence. Results: Likert scores with respect to image quality improved from 0.88 to 1.83 (p < 0.001) in high (130 and 150) keV images. High keV images reduced the number of false negative non-unions based on consolidation grade with 5% (p = 0.283). Agreement between observers regarding location of consolidation and non-union type did not improve in 130 and 150 keV images. Diagnostic confidence improved from 1.43 to 2.37 in high keV images compared to 70 keV images (p < 0.001). Overall diagnostic confidence was higher in intramedullary nails than plates (p < 0.05). Conclusions: Use of virtual monochromatic 130 and 150 keV dual-energy CT compared to 70 keV images improves the evaluation of suspected non-union of the appendicular skeleton treated with titanium or stainless steel intramedullary nails and plates.